MUTED VOICES: CAN THE SUBALTERN SPEAK? (A READING OF THE SHORT-STORY “TIO ME DÁ SÓ CEM” [JUST GIMME A HUNDRED], BY JOÃO DE MELO) - Danuza Américo Felipe de Lima; Jorge Vicente Valentim (Abril, 2014)
We propose in this paper an analysis of João Melo´s tale “Tio me dá só cem” part of the tale´s book titled Filhos da Pátria (2001), in accordance with the post-colonial theory and the assumptions discussed by Gayatry Spivak about the subordination and the subjects silenced by official discourses. We intend to see the resources used by the Angolan writer about childhoods from the point of view of the child in the context of social abandonment.